Phytochemical analysis, antioxidant, and antibacterial activities of crude and partially purified extracts of Portulaca oleracea leaves - BRAGAIS, EDWARD KEVIN; Alika Co, Kiana; Enriquez, Daphne Noreen; Labarda, Aubrey Love; Manongsong, Reanne Eden; B. Bragais, Edward Kevin (Academia Journal of Biology, 2025)
The increasing antibiotic resistance among pathogens has driven the search for natural alternatives, particularly plant-based antimicrobials. This study investigates the antioxidant and antibacterial activities of Portulaca oleracea, a plant renowned for its polyphenolic constituents. The leaves were extracted using solvents of varying polarities to obtain different fractions for analysis. Qualitative phytochemical screening revealed a rich profile of polyphenolic compounds, including flavonoids, tannins, phenolic acids, and anthocyanins. The crude methanolic extract exhibited significant (p < 0.05) antioxidant activities against DPPH (50.08 ± 2.49%), superoxide (42.61 ± 0.56%), and hydroxyl (6.60 ± 0.94%). Furthermore, this extract demonstrated antibacterial efficacy, displaying zones of inhibition (ZOI) against Staphylococcus aureus (8.95 ± 0.19 mm) and Escherichia coli (7.18 ± 0.26 mm). Meanwhile, the polyphenol-rich aqueous fraction exhibited the highest antioxidant activities among the tested extracts (p < 0.05) with potent antibacterial activities against S. aureus (ZOI = 11.21 ± 0.11 mm) and E. coli (ZOI = 10.21 ± 0.18 mm). The bioactivities may be linked to polyphenolic compounds like quercetin, herbacetin, and rhamnetin, as identified by UPLC-MS. The high total phenolic content (181.58 ± 5.34 mg GAE/g) in the aqueous fraction aligns with its strong antioxidant and antibacterial effects (p < 0.05). These results suggest the potential of P. oleracea as a natural source of antibacterial agents and warrant further investigation into its mechanisms of action.